RETRACTED: The Increase in IL-1β in the Early Stage of Heatstroke Might Be Caused by Splenic Lymphocyte Pyroptosis Induced by mtROS-Mediated Activation of the NLRP3 Inflammasome - Wang, Gong; Shen, Tingting; Li, Ping; Luo, Zhen; Tan, Yulong; He, Genlin; Zhang, Xiaoliang; Yang, Ju; Liu, Jun; Wang, Yuan; Tang, He; Luo, Xue; et al. (Frontiers in Immunology, 2019)
Interleukin-1β (IL-1β) is important for the pathological process of heatstroke(HS), although little is known regarding the main source of the IL-1β produced during the early stage of HS. In this study, heat stress led splenic lymphocyte to death with generation of inflammatory cytokines. The same phenomenon also occurs in animal models of heatshock. We observed that the death of splenic lymphocyte was identified to be pyroptosis. In addition, splenic lymphocyte pyroptosis can be induced by hyperpyrexia in a time- and temperature-dependent manner with NLRP3 inflammasome activation. NLRP3 inhibitor (MCC950) and caspase-1 inhibitor (ac-YVAD-cmk) were used to comfirm the role of NLRP3/caspase-1 pathway in pyroptosis. With heat stress, it would increase significantly that levels of mitochondrial reactive oxygen species (mtROS) in splenic lymphocytes. Accordingly, the use of mtROS scavenger (Mito-TEMPO) could reduce the occurrence of pyroptosis and the activation of the NLRP3 inflammasome in vitro. In animal models of heatshock, Mito-TEMPO can inhibit activation of NLRP3/caspase-1 pathway. Taken together, our data suggest that activation of the NLRP3 inflammasome mediates hyperpyrexia-induced pyroptosis in splenic lymphocytes. Perhaps one of the important initiators of pyroptosis is mtROS. Our data have elucidated a new molecular mechanism of IL-1β overexpression in the early stage of HS, providing a new strategy for IL-1β-targeted therapy in future clinical treatments for HS.